2022
DOI: 10.3233/wor-205300
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low back pain in India: A systematic review and meta-analysis

Abstract: BACKGROUND: Although many studies have investigated the prevalence of low back pain (LBP) among Indian subjects, no meta-analysis has been conducted to determine the comprehensive epidemiological point, annual, lifetime prevalence of LBP among Indian subjects. OBJECTIVE: The purpose of this systematic review and meta-analysis was to investigate the point, annual, and lifetime prevalence of LBP in the Indian population. METHODS: We searched PubMed, Embase, Science Direct, and Cochrane Library databases for rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 109 publications
2
10
0
Order By: Relevance
“…The present study demonstrates a high prevalence of LBP among the surveyed population in Tabuk city. The prevalence of LBP among our participants was 46.2% (95% CI: 42.7-49.8%), which is in line with that reported by a recent systematic review [19] in India (48%, 95% CI 40-56%). Meanwhile, a higher rate was reported by Awaji, [4] who found that the prevalence of LBP in Saudi Arabia ranged from 53.2% to 79.17%.…”
Section: Discussionsupporting
confidence: 91%
“…The present study demonstrates a high prevalence of LBP among the surveyed population in Tabuk city. The prevalence of LBP among our participants was 46.2% (95% CI: 42.7-49.8%), which is in line with that reported by a recent systematic review [19] in India (48%, 95% CI 40-56%). Meanwhile, a higher rate was reported by Awaji, [4] who found that the prevalence of LBP in Saudi Arabia ranged from 53.2% to 79.17%.…”
Section: Discussionsupporting
confidence: 91%
“…According to the World Health Organization report [10], musculoskeletal conditions are reported among 1.71 billion people across the globe, in which Low back pain is the main contributor with 570 million cases globally. As per the literature [11], the annual and lifetime prevalence of LBP in India stands at 51% (95% CI 45-58%) and 66% (95% CI 56-75%) respectively. [12] Intervertebral disc is largely avascular, hypoxia, low pH, high osmotic pressure and executes high mechanical load [13][14][15] and such an unique environment makes it challenging for the exogenous cell therapy to accomplish the objective i.e., treatment of IVDD.…”
Section: How To Citementioning
confidence: 82%
“… 1 According to a meta-analysis, the prevalence of LBP is approximately 48–66%. 2 Acute or chronic LBP affects the health of patients and causes an enormous impact on individuals and communities throughout the world. 1 Therefore, it is important to understand the pathological and pathophysiological mechanisms underlying the prevention and treatment of LBP.…”
Section: Introductionmentioning
confidence: 99%